Analisis Persepsi dan Kesiapan Guru Kimia Terhadap Implementasi Kurikulum 2013 Pada Era New Normal - Ayu Rahayu; Edi Ilimu; Musdalifatul Adewia; Titinawati Titinawati (Jurnal Ilmiah Wahana Pendidikan, 2022)
The peak of the pandemic has passed, now education has entered a new life order or a new normal where the government has issue a new policy, namely allowing the process of learning activities to be carry out face-to-face with a note that the health protocol has been determined. The purpose of this study was to determine the perception and readiness of chemistry teachers towards the implementation of the 2013 curriculum in the new normal era in terms of planning, implementation and evaluation of learning outcomes. The research sample was chemistry subject teachers from each of 5 different schools. This research are a type of qualitative descriptive research with data collection techniques in the form of interviews used interview sheet instruments, direct observation and documentation. The data analysis technique used is reduction, presentation and conclusion drawing and data verification. The results obtainable are related to the perception and readiness of chemistry teachers, which is the same as when the learning process before the covid19 pandemic was still preparing learning tools such as lesson plans based on scientific and 21st century skills while the learning process is carry out using models, teaching materials, and media that can improve student learning outcomes. In addition, the assessment is carry out authentically in 3 domains (knowledge, skills and attitudes).